2014
DOI: 10.4236/ijcm.2014.55038
|View full text |Cite
|
Sign up to set email alerts
|

Review: Do We Still Need a Viability Study before Considering Revascularization in Patient with Stable Coronary Artery Disease and Significant Left Ventricular Systolic Dysfunction?

Abstract: Patients with ischemic cardiomyopathy constitute a heterogeneous group of patients with an extremely complex condition in which many factors play an important prognostic role. So it is difficult and probably unrealistic to expect that a single feature like presence of viable myocardium would provide an unequivocal answer to a critical question of revasculrization or not for all patients. Opposite to the hopes of investigators and physicians involved in the care of these patients, the findings of prospective st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Some previous studies focused on myocardial viability, which could be indicated by the extent of postoperative improvement of EF, as an important predictor of survival after CABG for ischemic heart disease, although it remains controversial. [17][18][19][20][21] Our results suggested that it could be required for better survival to keep postoperative EF as high as possible, regardless of the postoperative change of this parameter. Therefore, in consideration of whether SVR should be added or not, the perspective that a higher postoperative EF could be estimated with SVR than without it could encourage surgeons to perform the procedure.…”
Section: Discussionmentioning
confidence: 67%
“…Some previous studies focused on myocardial viability, which could be indicated by the extent of postoperative improvement of EF, as an important predictor of survival after CABG for ischemic heart disease, although it remains controversial. [17][18][19][20][21] Our results suggested that it could be required for better survival to keep postoperative EF as high as possible, regardless of the postoperative change of this parameter. Therefore, in consideration of whether SVR should be added or not, the perspective that a higher postoperative EF could be estimated with SVR than without it could encourage surgeons to perform the procedure.…”
Section: Discussionmentioning
confidence: 67%